Toward a political philosophy of race - Sheth, Falguni A. 1968- (Albany, NY State University of new York Press, 2009)
"Timely, controversial, and incisive, Toward a Political Philosophy of Race looks uncompromisingly at how a liberal society enables racism and other forms of discrimination. Drawing on the examples of the internment of U.S. citizens and residents of Japanese descent, of Muslim men and women in the contemporary United States, and of Asian Indians at the turn of the twentieth century, Falguni A. Sheth argues that racial discrimination and divisions are not accidents in the history of liberal societies. Race, she contends, is a process embedded in a range of legal technologies that produce racialized populations who are divided against other groups. Moving past discussions of racial and social justice as abstract concepts, she reveals the playing out of race, racialization of groups, and legal frameworks within concrete historical frameworks."--Publisher's description.
Introduction: If You Don't Do Theory, Theory Will Do You 1 -- 1 The Technology of Race and the Logics of Exclusion: The Unruly, Naturalization, and Violence 21 -- First Dimension: Taming the Unruly 26 -- Second Dimension: Naturalizing the Unruly 28 -- Race as a Tool for Sovereign Power: Dividing Populations 29 -- Enframing Race: Vulnerability and Violence 35 -- 2 The Violence of Law: Sovereign Power, Vulnerable Populations, and Race 41 -- Law, Violence, and Undecidability 42 -- Sovereign Power 47 -- Unruly and Vulnerable Populations 49 -- The Racialization of a Population 51 -- The Unruly and the Vulnerable Manifested as Categories of Law: Immigrants, Aliens, Enemies 56 -- 3 The Unruly: Strangeness, Madness, and Race 65 -- Strangeness 67 -- Huntington and Rawls: Islam, Madness, and the Menace to Liberalism 74 -- Difference, Madness, and Race 78 -- Liberal Hegemony and Heterogeneous Populations 81 -- 4 The Newest Unruly Threat: Muslim Men and Women 87 -- The Racializing and Outcasting of Muslims in the United States 88 -- Culture, Heterogeneity, and the Foreigner: Unruly Women 95 -- 5 Producing Race: Naturalizing the Exception Through the Rule of Law 111 -- Exceptions and the Rule of Law 113 -- Constitutional Rights: Political? Human? 117 -- 6 Border-Populations: Boundary, Memory, and Moral Conscience 129 -- The Third Term: Pariah Populations as a Border-Guard 130 -- Pariahs, Border-Populations, and Moral Gauges: The Example of Black Americans 136 -- Furthering State Interests: Dividing Populations Against Each Other 141 -- Concealing and Unconcealing: Multiple Border-Guards and Outsiders 143 -- 7 Technologies of Race and the Racialization of Immigrants: The Case of Early Twentieth-Century Asian Indians in North America 147 -- The Great "Hindu" Migration 148 -- Political Resistance or Insurgency? 150 -- Racialization 154 -- Invisibility 157 -- Conclusion: Toward a Political Philosophy of Race 167.
Includes bibliographical references (pages 229-247) and index.
Keywords: Race discrimination -- United States; Race discrimination -- United States. -- Philosophy; Racism -- United States; United States -- Race relations